Biologically stable threose nucleic acid-based probes for real-time microRNA detection and imaging in living cells - Fei Wang; Ling Sum Liu; Pan Li; Hoi Man Leung; Dick Yan Tam; Pik Kwan Lo (Elsevier, 2022)
We successfully fabricated threose nucleic acid (TNA)-based probes for real-time monitoring of target miRNA levels in cells. Our TNA probe is comprised of a fluorophore-labeled TNA reporter strand by partially hybridizing to a quencher-labeled TNA that is designed to be antisense to a target RNA transcript; this results in effective quenching of its fluorescence. In the presence of RNA targets, the antisense capture sequence of the TNA binds to targeted transcripts to form longer, thermodynamic stable duplexes. This binding event displaces the reporter strand from the quencher resulting in a discrete "turning-on" of the fluorescence. Our TNA probe is highly specific and selective toward target miRNA and is able to distinguish one to two base mismatches in the target RNA. Compared with DNA probes, our TNA probes exhibited favorable nuclease stability, thermal stability, and exceptional storage ability for long-term cellular studies. Our TNA probes are efficiently taken up by cells with negligible cytotoxicity for dynamic detection of target miRNAs and can also differentiate the distinct target miRNA expression levels in different cell lines. This work illuminates for using TNA as a building component to construct a biocompatible probe for miRNA detection that offers alternative molecular reagents for miRNA-related diagnostics.